Drug transporters play a key role in the complex process of Imatinib resistance in vitro. Issue 3 (March 2015) - Alves, Raquel; Fonseca, Ana Raquel; Gonçalves, Ana C.; Ferreira-Teixeira, Margarida; Lima, Joana; Abrantes, Ana M.; Alves, Vera; Rodrigues-Santos, Paulo; Jorge, Lénia; Matoso, Eunice; Carreira, Isabel M.; Botelho, Maria Filomena; et al.
Highlights We establish the first Imatinib resistant cell line by discontinuous exposure. This model elucidated the importance of treatment interruptions in resistance. In both resistant models, efflux transporters were increased comparing to K562. Influx transporters expression were diminished in both resistant cell lines. Our results show the importance of ABC transporters as therapeutic targets.